Linking Self-Construal to Creativity: The Role of Approach Motivation and Cognitive Flexibility - Shao, Yan; Nijstad, Bernard A.; Täuber, Susanne (Frontiers in Psychology, 2018)
While some evidence has linked the way individuals define themselves in relation to others (independent versus interdependent self-construal) to creativity, little is known about the underlying mechanism in explaining why and how self-construal influences creativity. Integrating approach-avoidance motivation theory and the dual pathway to creativity model, this research focuses on the motivational and cognitive mechanisms that transfer the effects of self-construal on creativity. Specifically, we expect that independent self-construal is a driver of creativity because it facilitates individuals’ approach motivation, which in turn increases flexible information processing. To test the three-stage mediation model, one experiment and one survey study were conducted. In Study 1, in a sample of 231 Dutch students, self-construal was manipulated by a story-writing task; approach-avoidance motivation, cognitive flexibility and creativity were measured. In Study 2, self-construal, approach (and avoidance) motivation, cognitive flexibility and creativity were all measured in a second sample of Dutch students (N = 146). The results of two studies supported the three-stage mediation model, showing that approach motivation and cognitive flexibility together mediated the effects of self-construal on creativity. Limitations and implications for future research are discussed.